ALGORITHM OF RESTORATION PERIODIC A SIGNAL IN ROTARY SYSTEMS - M.V. CHUVEYKO (Advanced Engineering Research)
Given clause is devoted to a statement of algorithm of restoration of a periodic component of a signal in systems with an additive handicap of peak character at absence of aprioristic data on frequency of a restored signal.